PENGARUH DISIPLIN,KOMPETENSI DAN KREATIVITAS MENGAJAR TERHADAP KINERJA GURU DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 1 KARANG BARU KECAMATAN KARANG BARU KABUPATEN ACEH TAMIANG - Sutiyah . (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
A nation no longer relies on the superiority of natural wealth, but rather on the excellence of human resources, one of which is educators (teachers) who are able to answer challenges very quickly. Education is basically an effort to develop human resources, even though efforts to develop human resources. Problems regarding teacher performance are problems that will always be faced by the management of an organization, therefore management needs to know the factors that can affect teacher performance With withdrawal techniques sample in total sampling, the sample in this study amounted to 30 people Middle School 1 Junior High School Teacher Karang Baru District Karang Baru Aceh Tamiang District. There was a significant effect of Discipline on the performance of teachers in the Junior High School 1 Junior High School at 0.353 on teacher performance so that it can be concluded adequate discipline can determine Teacher performance will also be high even though there are other variables that support to see the results of the performance of a teacher -0.281 but it is significant to conclude that Compensation can have high results if the teacher has good Compensation. Teacher creativity influences teacher performance by 0.351 and this significant indicates that Creativity can improve performance, Discipline, Compensation and Creativity together - a significant effect on teacher performance at SMP Negeri 1 Karang Baru First Middle School, is 24.6% while the remaining 75.4% is explained by other variables not included in this research model.